2021
DOI: 10.18203/2394-6040.ijcmph20214990
|View full text |Cite
|
Sign up to set email alerts
|

Association of minimum dietary diversity and minimum meal frequency with anthropometric parameters among children of 6 to 23 months of age attending immunization clinic of a tertiary care hospitals

Abstract: Background: The age of 6–23 months is the golden period in the first 1000 days of life. Insufficient quantities, frequencies, and inadequate quality of complementary feedings have a negative effect on child health and growth, especially in the first two years of life.Methods: A hospital based descriptive type of observational study was carried out in the immunization clinic. The source population were the mothers who had children in age group of 6-23 months brought to the clinic in the month of January 2021 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This higher than in Ethiopia (18.2%), Liberia (8.6%), Gambia (20.2%), Rwanda (34.4%), Kenya (17.9%), Zambia (12%), Afghanistan (27.6%), Ghana (34.8%) and Zimbabwe (28%) [16,56]. Diversi cation of diets is a long-term sustainable strategy to reduce micronutrient de ciencies and optimise growth and health for all human being particularly children [54].…”
Section: Discussionmentioning
confidence: 99%
“…This higher than in Ethiopia (18.2%), Liberia (8.6%), Gambia (20.2%), Rwanda (34.4%), Kenya (17.9%), Zambia (12%), Afghanistan (27.6%), Ghana (34.8%) and Zimbabwe (28%) [16,56]. Diversi cation of diets is a long-term sustainable strategy to reduce micronutrient de ciencies and optimise growth and health for all human being particularly children [54].…”
Section: Discussionmentioning
confidence: 99%
“…A very diverse diet is reflected in the high diversity of foods as a guide to micronutrient intake, the diversity of foods reveals whether children receive a complete and balanced diet or not (Solanki et al, 2022). Khalil et al (2022) reported that children aged 6-59 months who consumed a variety of foods had an appropriate height when compared to children who did not get a variety of complementary foods.…”
Section: The Effect Of Low Variety Types Of Complementary Foods On Th...mentioning
confidence: 99%
“…Minimum meal frequency is a proxy for a child's energy needs. The indicator is based on how much energy a child needs (Solanki et al, 2022).…”
Section: The Effect Of Low Frequency Of Giving Complementary Foods On...mentioning
confidence: 99%